Physiological Effects of Nonimmune Platelet Associated Immunoglobulin G - Sugiura, K; Steiner, M; Baldini, M (Thrombosis and Haemostasis, 1981)
The function of nonimmune IgG associated with platelets is unknown. In a series of experiments we have investigated this problem, relating amount of platelet-associated IgG (PAIgG) to platelet volume, serotonin release, adherence of platelets to monocytes and platelet senescence. Most of these studies were performed with human platelets. Platelets freed of preexisting PAIgG by incubation at 22° C were incubated with IgG in a series of concentrations ranging from 0.4 — 27.0 X10-6 M. The IgG preparations used were demonstrably free of aggregated forms of the protein. The amount of PAIgG bound to platelets was determined by the use of fluorescein isothiocyanate-conjugated anti-IgG antibody (F-anti-IgG antibody) which was quantified in a fluorospectrophotometer. Newly bound IgG was assayed similarly by the use of F-IgG. A dose-dependent increase in platelet volume was associated with the binding of nonimmune IgG by platelets. The process which leveled off at an IgG concentration of 1.2 —1.5 X10-5 M was almost fully reversible and was not due to platelet shape change or aggregation. Release of serotonin from IgG-treated platelets was relatively small but to the extent that it occurred was positively related to the IgG concentration to which platelets were exposed. Adherence to autologous monocytes studied quantitatively by the use of formaldehyde-fixed cells was also positively related to the amount of IgG on the platelets. Normal or IgG-defident serum had a potent inhibitory (noncompetitive) action on the binding of F-IgG and F-anti-human IgG antibody to human platelets. Cohorts of platelets prepared in rabbits during the recovery phase of immunological thrombocytopenia induced by injection of heterologous antiserum, showed an age-dependent increase of PAIgG and of IgG binding. These results suggest that PAIgG plays a role in the clearance of senescent platelets.
Keywords: Platelets; Platelet-associated IgG; Nonimmune IgG; Platelet senescence; Physiological effect